Integrating Palliative Care into the Care of Neurocritically Ill Patients: A Report from The IPAL-ICU (Improving Palliative Care in the Intensive Care Unit) Project Advisory Board and the Center to Advance Palliative Care - Frontera, Jennifer A. (Crit Care Med, 2015)
OBJECTIVES: To describe unique features of neurocritical illness that are relevant to provision of high-quality palliative care; To discuss key prognostic aids and their limitations for neurocritical illnesses; To review challenges and strategies for establishing realistic goals of care for patients in the neuro-ICU; To describe elements of best practice concerning symptom management, limitation of life support, and organ donation for the neurocritically ill. DATA SOURCES: A search of Pubmed and MEDLINE was conducted from inception through January 2015 for all English-language articles using the term “palliative care,” “supportive care,” “end-of-life care,” “withdrawal of life-sustaining therapy,” “limitation of life support,” “prognosis,” or “goals of care” together with “neurocritical care,” “neurointensive care,” “neurological,” “stroke,” “subarachnoid hemorrhage,” “intracerebral hemorrhage,” or “brain injury.” DATA EXTRACTION AND SYNTHESIS: We reviewed the existing literature on delivery of palliative care in the neurointensive care unit setting, focusing on challenges and strategies for establishing realistic and appropriate goals of care, symptom management, organ donation, and other considerations related to use and limitation of life-sustaining therapies for neurocritically ill patients. Based on review of these articles and the experiences of our interdisciplinary/interprofessional expert Advisory Board, this report was prepared to guide critical care staff, palliative care specialists, and others who practice in this setting. CONCLUSIONS: Most neurocritically ill patients and their families face the sudden onset of devastating cognitive and functional changes that challenge clinicians to provide patient-centered palliative care within a complex and often uncertain prognostic environment. Application of palliative care principles concerning symptom relief, goal setting, and family emotional support, will provide clinicians a framework to address decision-making at a time of crisis that enhances patient/family autonomy and clinician professionalism.